Dynamics of IgG antibody response against Plasmodium antigens among Nigerian infants and young children - Leonard, Colleen M.; Uhomoibhi, Perpetua; Abubakar, Ado; Ogunniyi, Abiodun; Mba, Nwando; Greby, Stacie M.; Okoye, McPaul I.; Iriemenam, Nnaemeka C.; Ihekweazu, Chikwe; Steinhardt, Laura; Rogier, Eric; , NMS4 Technical Working Group (Frontiers in Immunology, 2023)
Background: Plasmodium falciparum malaria is a leading cause of child mortality in Nigeria.Neonates are born with maternal antibodies from placental transfer which may protect against malaria infection in the first months of life. The IgG dynamics of the transition from passively transferred antimalarial antibodies to actively acquired IgG from natural exposure has not been well elucidated. Methods: Blood samples collected during a 2018 Nigeria nationwide HIV/AIDS household survey were available for 9,443 children under five years, with a subset of infants under two months of age having maternal samples available (n=41). Samples were assayed for the P. falciparum HRP2 antigen and anti-malarial IgG antibodies. LOESS regression examined dynamics in IgG response for the first five years of life. Correlation with maternal IgG levels was assessed for mother/child pairs. Results: Consistent decreases were observed in median IgG levels against all Plasmodium spp. antigen targets for the first months of life. At a population level, P. falciparum apical membrane antigen-1 (AMA1) and merozoite surface protein-1 19kD (PfMSP1) IgG decreased during the first 12 months of life before reaching a nadir, whereas IgGs to other targets only declined for the first four months of life. Seropositivity showed a similar decline with the lowest seropositivity against AMA1 and PfMSP1 at 10-12 months, though remaining above 50% during the first two years of life in higher transmission areas. No protective association was observed between IgG positivity and P. falciparum infection in infants. Maternal antibody levels showed a strong positive correlation with infant antibody levels for all P. falciparum antigens from birth to two months of age, but this correlation was lost by six months of age. Discussion: Maternally transferred anti-malarial IgG antibodies rapidly decline during the first six months of life, with variations among specific antigens and malaria transmission intensity. From 3-23 months of age, there was a wide range in IgG levels for the blood-stage antigens indicating high individual variation in antibody production as children are infected with malaria. Non-falciparum species-specific antigens showed similar patterns in waning immunity and correlation with paired mother's IgG levels compared to P. falciparum antigens.